Is survival after transanal total mesorectal excision (taTME) worse than that after traditional total mesorectal excision?: A retrospective propensity score-adjusted cohort study - Ammann, Yanic Rolf; Warschkow, René; Schmied, Bruno; De Lorenzi, Diego; Reißfelder, Christoph; Bischofberger, Stephan; Marti, Lukas; Brunner, Walter (Electronic journal of statistics, 2024)
Transanal total mesorectal excision (taTME) was developed to provide better vision during resection of the mesorectum. Conflicting results have shown an increase in local recurrence and shorter survival after taTME. This study compared the outcomes of taTME and abdominal (open, laparoscopic, robotic) total mesorectal excision (abTME).
Publikationsdatum: 20. Februar 2010 (Online)
Gesehen am 15.10.2024